A feedback controller for milling chatter vibration control using a new response matrix. (May 2022) - Muhammad, Bashir B; Bashir, Muhammad; Hamza, Mukhtar F; Abdulhadi, Mustapha; Shehu, Muhammad A; Debnath, Sanjoy K; Bagchi, Susama
A chatter mark is a result of irregular vibration that affects the milling process, which results in poor surface finish, reduced work quality, machine impairment, and high production cost. This work presents an active feedback controller design using a new response matrix to suppress the free vibration in the milling process. The proposed controller considers feed rate, tooth passing frequency, and time-varying dynamic milling force coefficients. A milling experiment verifies the effect of the proposed method. The method provides a reliable way of tackling chatter vibration in an industrial process. The procedure is technically and economically beneficial.